Combined bone marrow mesenchymal stem cell-derived nanovesicles and low-level laser therapy potentiate proliferation and osteogenesis of bone marrow mesenchymal stem cells - Zhang, Jingwei; Yao, Tonghao; Han, Qi; Mo, Yongqiang; Li, Dailuo; Zhang, Zhengye; Cui, Lihuang; Geng, Zhibin; He, Weitao; Chen, Jingtao; Liu, Xin; Wang, Xintao (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAddressing the persistent challenge of bone defect repair requires innovative bioengineering strategies. Enhancing the biological activity of bone marrow mesenchymal stem cells (BMSCs) is pivotal for effective bone regeneration. This study develops a novel combinatorial bioengineering approach leveraging two distinct biotechnological modalities: low-level laser therapy (LLLT) and bone marrow mesenchymal stem cell-derived nanovesicles (BMSC-NVs). LLLT, a non-invasive biophysical stimulation technique with defined light parameters, is known to prime cellular responses. Concurrently, BMSC-NVs represent an emerging engineered cell-free therapeutic platform with significant promise for tissue regeneration. Thus, we hypothesize that combining LLLT’s direct regulatory effects on BMSCs with the bioactive cargo of BMSC-NVs will synergistically enhance BMSC function. This study presents the first evaluation of the combined impact of LLLT and BMSC-NVs on the proliferation and osteogenic differentiation of rat BMSCs in vitro.MethodsCell proliferation was quantified using CCK-8 assay, while osteogenic differentiation was assessed through alkaline phosphatase staining, alizarin red staining, and real-time quantitative polymerase chain reaction (osteogenic gene expression).ResultsThe LLLT+BMSC-NVs combinatorial strategy effectively enhances BMSC proliferation capacity (as indicated by increased OD values measured via CCK-8 assay), ALP activity, mineralized nodule formation, and upregulation of key osteogenic genes (ALP, RUNX2), showing superior effects on both proliferation and osteogenic differentiation compared to individual LLLT or BMSC-NVs treatments.ConclusionThis study proposes a novel cell-free therapeutic paradigm by synergistically integrating LLLT with BMSC-NVs, suggesting an effective bioengineering strategy for bone defect repair.